Harmoni Hindu-Muslim Berbasis Tradisi Lisan Sejarah Desa Saren Budakeling Karangasem Bali - Maknun, Moch Lukluil (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
One form of Hindu-Muslim harmony that is interesting to be photographed in Bali is what happened in the village of Saren Budakeling Bebandem Karangasem. This article aims to reveal the character values in the oral tradition of the history of the village of Saren which is the foundation of harmony among religious people. The problems discussed are limited to story motif ethnographically, the value of the oral traditions character, its interconnection with character education, and the inheritance value system. By utilizing ethnographic methods that have an interest in recording, understanding, and utilizing the value of local wisdom in the oral tradition, the following results are obtained. First, the oral history of the village's history brings together kinship relationships built by characters in the story, between local Hindus and immigrant Muslims who are the ancestors of the people there. Second, there is an interconnection of this oral tradition with character values, that this story contains many character values that strengthen the foundation of brotherhood of its citizens that manifests in daily life. Third, the inheritance of this story continues to be passed on from generation to generation, both verbally and written in the ejection.